Modified α-ψ-contractive mappings with applications - Salimi, Peyman; Latif, Abdul; Hussain, Nawab (Fixed point theory and applications (Hindawi Publishing Corporation), 2013)
The aim of this work is to modify the notions of α -admissible and α - ψ -contractive mappings and establish new fixed point theorems for such mappings in complete metric spaces. Presented theorems provide main results of Karapinar and Samet (Abstr. Appl. Anal. 2012:793486, 2012) and Samet et al. (Nonlinear Anal. 75:2154-2165, 2012) as direct corollaries. Moreover, some examples and applications to integral equations are given here to illustrate the usability of the obtained results. MSC: 46N40, 47H10, 54H25, 46T99.